Cloning immunoglobulin gamma 2b chain gene of mouse: characterization and partial sequence determination. - Kataoka, T (1979)
DNA from newborn mice was digested with restriction endonuclease EcoRI, and a 6.6-kilobase fragment encoding immunoglobulin gamma 2b chain mRNA derived from MPC 11 myeloma was enriched about 100-fold by RPC-5 column chromatography and agarose gell electrophoresis. The 6.6-kilobase fragment was cloned with lambda gt WES.lambda B as EK2 vector. The cloned phage (lambda WES.IgH22) contained the constant region gene of the gamma 2b chain but not the variable region gene of MPC 11 mRNA. The constant region genes of the other gamma chains (i.e., gamma 1, gamma 2a, and gamma 3) were not present in lambda gt WES.IgH22 DNA. R-loop mapping indicates that the gamma 2b chain structural gene is divided into two parts (330 +/- 60 SD base pairs and 930 +/- 110 SD base pairs) by an intervening sequence (360 +/- 100 SD base pairs). The nucleotide sequence around the junction of the hinge region and CH2 domain was determined and shown to match the amino acid sequence of the initial part of the CH2 domain of the gamma 2b chain. The base sequence upstream from the junction, however, is unrelated to the amino acid sequence of the CH1 domain and the hinge region of all the gamma chains whose sequences have been determined. These results indicate that the gamma 2b chain gene is interrupted at the junction of the hinge region and CH2 domain by an intervening sequence. The existence of two more intervening sequences, one between the CH1 domain and the hinge region and the other between the CH2 and CH3 domains, is discussed.